Knowledge, belief's attitudes and practices of dengue fever among the orang asli in Peninsular Malaysia / Josephine Rebecca - Josephine, Rebecca (2016)
Dengue is prevalent among Malaysia's indigenous people, known as the Orang Asli, and it poses a serious health threat to them. The study aims to look at the socio-demographic factors, health beliefs, and knowledge about dengue and its association to dengue prevention practices among Orang Asli communities in Peninsula Malaysia. A crosssectional survey was conducted in 16 randomly selected Orang Asli villages from eight states in Peninsula Malaysia from April 2012 until February 2013. A total of 560 Orang Asli were interviewed and 505 completed the survey. Overall dengue knowledge score among the respondent were low; tribes, occupational status and average monthly household income significantly correlated to dengue knowledge. The Semoq Beri tribe (OR=11.137, 95% CI= 2.98-41.61), was more likely to have higher dengue knowledge compared to the reference group (Kensui tribe). Skilled workers (OR=3.66, 95 % CI=1.07-12.52) were more likely to have higher dengue knowledge compared to the reference group (unemployed). However, those with income less than RM500 (OR=0.60, 95%CI = 0.39-0.94) were less likely to have dengue knowledge compared to the reference group (RM500 - RM1200). With regards to the constructs of HBM, majority of the Orang Asli respondents had perceived dengue severity score of 6-10 (n=445, 88.1%) and only 11.9 % had perceived dengue severity score of 1-5 (n=60). 82.0% of respondents had a score of 1-5 for perceived susceptibility towards dengue (n=414) while only 18.0 % of the Orang Asli respondents had score of 6-10 for perceived susceptibility towards dengue (n=91). Majority of the Orang Asli respondents had score of 1-5 for perceived barriers to prevent dengue (n=435, 86.1%) and only 18.0% (n=70) of the respondents had score 6-10 for perceived barriers to prevent dengue. Majority of the Orang Asli respondents “Disagree and strongly disagree” that there is a lack of self –efficacy in taking preventive measures against dengue (n=376, 74.5%). Overall dengue prevention practices were slightly high; perceived barriers to iv prevent dengue, knowledge score and tribes were factors which were significant correlate to dengue prevention practices. Respondent with low perceived barrier (OR=1.867, 95% CI= 1.051-3.317) were more likely to carry out dengue prevention practices. Respondents with low knowledge score (OR=0.522, 95% CI= 0.343-0.794) were less likely to carry out dengue prevention practices. Respondents from the Jakun tribe (OR=0.167, 95% CI= 0.054-0.514) and Temuan tribe (OR=0.407, 95% CI= 0.181- 0.916) were less likely to carry out dengue prevention practices compared to the reference group (Kensui tribe). Findings imply that efforts to enhance dengue prevention practices should focus on eliminating the foremost important factors which are the perceived barriers to prevent dengue and lack of knowledge of dengue. Intervention should focus on educating the Orang Asli to remove barriers to prevent dengue and impart more knowledge of dengue.